Educational and Career Trajectories of the Students Completed Vocational and Then College Degree - Elizaveta Korotkikh (Journal of Economic Sociology, 1970)
This research is aimed at studying the transit trajectory of students’ progress to higher education after achieving vocational qualification. The purpose of this study is to identify factors related to the choice of transit educational trajectory (socio-economic status, academic achievement, personal characteristics) and to assess the return of transit trajectory on the earnings of graduates. In this research, a transit educational route is classified into two types—completed transit (admitted to the university immediately after graduation from college) and continuing transit (admitted to the university some time after graduation). Data for the study were obtained during the national panel within the research project “Trajectories in education and occupation” (TrEC). Regression analysis is used as a method. There is a significant correlation between the transit trajectory and the student’s high socio-economic status (compared to those with only a TVET diploma) and school performance. Elowever, the entry into transit is more dependent on socio-economic status, as the importance of learning outcomes is significantly reduced when this variable is added to the model. Thus, the transit educational route is not a channel of social mobility, but rather a tool of reproduction of high-status positions. The work experience of a “transit” graduate gives a significant return on wages, but graduation from college by 24 years does not create such a return. Thus, in terms of human capital theory, recent “transit” collegecollege graduates have a more specific human capital return compared to those who completed their education and accumulated total human capital.